BIJAK MENGGUNAKAN KOSMETIK DAN SUPLEMEN KESEHATAN - rashati Dewi; Asa Falahi; anies Rohman Dwijayanti; Mikhania Christiningtyas Eryani (LPPM Universitas dr. Soebandi, 2026)
Teenagers are the next generation and the determining factor of the nation's future. The use of supplements and cosmetics is an important matter for teenagers to fulfill. The consumption of supplements by teenagers is a form of daily nutritional fulfillment activity. The use of cosmetics also attracts the attention of teenagers. The aim of this community service is to provide education on SMK Farmasi dr. Soebandi student to be wise in using cosmetics and health supplements. The method in this activity using explanation method and quantitative questionnaire data collection. This activity has a positive impact on increasing student knowledge also awareness of the importance of choosing and using cosmetics and supplements safely. That can be seen the increase pre-post test score from 63 to 80. Although the increase knowledge statistically is not significant, but this activity enhances participants understanding and encourages more rational consumer behavior.